Vegan menu marketing strategies for tourists to support green tourism in Loving Hut Restaurant in Denpasar Bali - Sumawidari, Ida Ayu Ketut; Sudarmini, Made; Pugra, I Wayan; Nadra, Nyoman Mastiani; Damayanti, Ida Ayu Kade Werdika; Susyarini, Ni Putu Wiwiek Ary (International Journal of Green Tourism Research and Applications, 2023)
The purpose of this study is to formulate a marketing strategy for vegan menus for tourists to support green tourism for Loving Hut restaurants in Denpasar. Data were collected using interviews, observations, questionnaires, and documentation. Then the data obtained were analyzed using: descriptive statistics, qualitative descriptive, IFE matrix, EFE matrix, IE matrix and SWOT analysis. The results of the analysis show that (1) tourists' perceptions of the vegan menu of non-animal products at Loving Hut restaurants are in the good category; (2) Loving Hut Restaurant in Denpasar is in cell II of the IE matrix, namely a growth strategy with product development through product differentiation or innovation is the right strategy. Alternative strategies that can be done are (a) expanding the market; (b) increasing promotional activities; (c) set competitive prices; (d) maximize the use of space; (e) adding suppliers; (f) improve services; and (g) improving the quality of human resources. There are several suggestions that can be given to improve the business going forward, including (1) utilizing e-commerce (social media, web) for promotion; (2) establish cooperation with existing travel agencies; (3) involve employees in trainings held by the government/educational institutions; (4) making product packages; and (5) recruiting marketers. It appears that Loving Hut restaurant can position itself strategically for growth through product development with a focus on differentiation and innovation.